Hannah - Lasky, Kathryn (New York Scholastic Press, 2009)
In 1899, a fifteen-year-old orphan named Hannah obtains employment as a servant in the home of one of Boston's wealthiest families, where she meets a noted portrait painter who seems to know things about her that even she is not aware of, and when she accompanies the family to their summer home in Maine, she feels an undeniable pull to the sea
Hurg
5 8
Keywords: Household employees -- Fiction; Identity -- Fiction; Mermaids -- Fiction